Atopic Dermatitis-Related Problems in Daily Life, Goals of Therapy and Deciding Factors for Systemic Therapy: A Review - Liborija Lugović-Mihić; Ema Barac; Renata Tomašević; Ena Parać; Lucija Zanze; Ana Ljevar; Lorena Dolački; Maja Štrajtenberger (Pharmaceuticals)
Background/Objectives/Methods: Atopic dermatitis (AD) impacts various aspects of patients’ lives including personal life, psychological aspects/disturbances (e.g., depression, anxiety, or even suicidal thoughts), school, and work-related activities, including career advancement. The aim of this narrative review is to present the latest information available on how to best approach AD patient management, as well as decisions regarding standard/advanced systemic therapy, by gathering evidence from the relevant medical literature (PubMed and other prominent medical databases). Results: Thus, AD patient management and decisions regarding advanced/systemic therapy are complex, requiring the consideration of multiple disease-related factors: age; disease severity; patient medical history and comorbidities; previous topical therapy use and any adverse reactions; treatment efficacy concerns; patient preferences, expectations and fears; pregnancy planning; ability and willingness to adhere to the treatment regimen; impact on related risks; and any associated psychological or psychiatric issues. Current guidelines and systematic reviews support the safety and efficacy of systemic therapy including conventional drugs (cyclosporine, methotrexate, and azathioprine), biologics (dupilumab and tralokinumab), and JAK inhibitors (baricitinib, upadacitinib, and abrocitinib) recommended for treating moderate and severe AD. Recently, additional biologics have been evaluated in clinical trials, including lebrikizumab, nemolizumab, eblasakimab, and OX40/OX40L, among others. Conclusions: The most recently suggested approach to treating AD patients suggests focusing on therapy that targets and achieves minimal disease activity (MDA), where therapy decisions are informed by both the patient and the clinician. Available data also indicate the importance of a personalized, stepwise, and multidisciplinary approach. This type of approach promotes patient compliance, satisfaction with therapy, and increased engagement, which all lead to better patient outcomes.